Robust finite-time boundedness of multi-agent systems subject to parametric uncertainties and disturbances. Issue 10 (26th July 2016) - Lee, Liming; Kou, Kit Ian; Zhang, Wentao; Liang, Jinling; Liu, Yang
Abstract : In this paper, we consider finite-time control problems for linear multi-agent systems subject to exogenous constant disturbances and impulses. Some sufficient conditions are obtained to ensure the finite-time boundedness of the multi-agent systems, which could be then reduced to a feasibility problem involving linear matrix inequalities. Numerical examples are given to illustrate the results.